Women’s autonomy in healthcare decision making: a systematic review - Idris, Idayu Badilla; Hamis, Amy Azira; Bukhori, Ayuzeity Bistari Md; Hoong, David Chan Chee; Yusop, Hakimah; Shaharuddin, Muhammad Al-Amin; Fauzi, Nazmeen Adline Fawwazah A.; Kandayah, Thinakaran (BMC women's health, 2023)
Although there are calls for women's empowerment and gender equity globally, there are still large disparities regarding women's autonomy in healthcare decision making. The autonomy of women is believed to be crucial in improving their health-related outcomes. This review discusses factors that influence autonomy among women in healthcare decision making. Systematic review. PubMed, Web of Science and Scopus were searched from 2017-2022. The inclusion criteria include original articles, case studies and reports that has been written in the English Language, while manuscripts with no full article, reviews, newspaper reports, grey literatures, and articles that did not answer the review objectives were excluded. We carried out data extraction using a standardized data extraction form, that has been organized using Microsoft Excel. A narrative synthesis was carried out to combine the findings of all included articles. A total of 70 records were identified and 18 were reviewed, yielding eight articles to be included in the accepted list of studies. All studies were conducted in developing countries and most of the studies were cross sectional. Factors that were associated with women's autonomy in healthcare decision making were age, women's education and occupation, husbands'/partners' education and occupation, residential location or region of residence, household wealth index as well as culture and religion. Identification of these factors may help stakeholders in improving women's autonomy in healthcare decision making. Policymakers play a crucial role in healthcare decision making by enacting laws and policies that protect women's rights, promoting gender-sensitive healthcare services, ensuring access to comprehensive information, promoting health education, and supporting vulnerable populations. These efforts ensure women's autonomy including able to access to unbiased and effective healthcare services.